Sputtering an exterior metal coating on copper enclosure for large-scale growth of single-crystalline graphene. (19th September 2017) - Luo, Birong; Caridad, José M; Whelan, Patrick R; Thomsen, Joachim Dahl; Mackenzie, David M A; Grubišić Čabo, Antonija; Mahatha, Sanjoy K; Bianchi, Marco; Hofmann, Philip; Jepsen, Peter Uhd; Bøggild, Peter; Booth, Timothy J
Abstract: We show the suppression of nucleation density in chemical vapor deposited graphene through the use of a sputtered metal coating on the exterior of a copper catalyst enclosure, resulting in the growth of sub-centimeter scale single crystal graphene domains and complete elimination of multilayer growth. The sputtered coating suppresses nucleation density by acting as both a diffusion barrier and as a sink for excess carbon during the growth, reducing the carbon concentration in the interior of the enclosure. Field effect mobility of hBN-templated devices fabricated from graphene domains grown in this way show room temperature carrier mobilities of 12 000 cm 2 V −1 s −1 and an absence of weak localization at low temperature. These results indicate a very low concentration of line and point defects in the grown films, which is further supported by Raman and transmission electron microscopic characterization.